PENERAPAN METODE PIECES UNTUK ANALISIS TINGKAT KEPUASAN PENGGUNA DALAM APLIKASI MOBILE BANKING MANDIRI - Azzahrah, Fatimah; M. Rudi Sanjaya; Dedy Kurniawan; Dwi Rosa Indah (AI Society & STMIK Indonesia, 2025)
This study analyzes users of the application known as Livin’ by Mandiri using the PIECES method, which includes indicators in the form of “Performance, Information, Economy, then also Control, Efficiency, and Service”. The researchers used a Likert scale via an online questionnaire by distributing the questionnaire to 201 active app users, supported by relevant literature. The research instrument was tested for validity and reliability, and all parameters were found to be valid and reliable. Descriptive quantitative analysis showed high satisfaction, particularly on the Efficiency (4.30) and Performance (4.26) indicators. The PIECES method proved effective in identifying key aspects that influence user satisfaction, offering recommendations for the development of digital services. Bank Mandiri and various other banks can use this discovery to create improved service quality with technology base that makes customers feel satisfied because their needs can be served more optimally.